Correlated evolution of parental care with dichromatism, colors, and patterns in anurans. (15th March 2022) - Shamanna Seshadri, Kadaba; Thaker, Maria
Abstract: Parental care is widespread and has fitness benefits. But caregiving parents incur costs including higher predation, and this may lead to selection for body colors or patterns that help mitigate the risks of caring. The evolution of coloration, including sexual dichromatism, however, can be driven by other factors, such as sexual selection. Therefore, examining the associations between parental care and color patterns may provide key insights into evolutionary patterns and selection pressures for parental care. Our comparative analysis of 988 anuran species reveals that dichromatic species are less likely to provide parental care, irrespective of the caregiving sex, and are more likely to breed in aquatic habitats. We then examined whether dorsal colors and patterns that enhance crypticity or function as aposematic signals are associated with the caregiving sex, and the modality of care (transport or stationary). Only caregiving males are more likely to have dorsal Stripes, but none of the colors (Green‐Brown, Red, Yellow, Blue‐Black) and other patterns (Plain, Bands, Spots, Mottled‐Patches) were associated with caregiving females or the modality of care. Overall, sexual dichromatism, breeding ecology, and parental care are associated, but the evolution of caregiving behavior does not appear to influence the myriad colors and patterns characteristic of anurans globally.